Effects of Dendrobium officinale Kimura & Migo flower flavonoids on cognitive function by regulating gut microbiota - Hu, Nanzhi; Wang, Kaiyue; Ge, Xing; Zhang, Xin; Zheng, Xiaojie; Sun, Shifang (Frontiers in Pharmacology, 2025)
BackgroundAs we get older, we experience a variety of symptoms such as memory and cognitive decline in learning. In the process of aging, neuroinflammatory response is one of the main reasons for the occurrence of cognitive dysfunction. Dendrobium officinale Kimura & Migo flower flavonoids (DOFF) can effectively regulate the structure of intestinal microbiota, antioxidant and anti-inflammatory functions.MethodsDOFF samples were extracted by water extraction assisted ultrasonic ethanol method. The DOFF composition was determined by LC-MS/MS method. An aging mouse model was established using D-galactose (D-gal) induced mice. 16S rDNA sequencing was used to analyze intestinal flora, hematoxylin/eosin staining (H&E) and immunohistochemical staining were used to analyze colonic and hippocampal tissue damage and related proteins, and ElISA was used to determine related inflammatory factors. The Y-maze experiment was used to test the cognitive ability of mice, the expression of related synaptic protein was detected by WB, and Iba-1 was labeled by immunofluorescence to study the effects of DOFF on inflammatory response and cognitive function by regulating intestinal microbiota.ResultsThe results showed that DOFF intervention could regulate the relative abundance of intestinal flora in D-gal mice, including the relative abundance of Akkermansia, down-regulate the ratio of Firmicutes/Bacteroidetes, up-regulate the expression of ZO-1, and improve the colonic tissue injury. In addition, by inhibiting the production of MDA, increasing the activity of SOD, CAT and POD, inhibiting the expression of pro-inflammatory factors TNF-α, IL-6 and IL-1β, inhibiting the activation of microglia, and effectively improving the oxidative stress damage and inflammation caused by aging. By increasing the expression of related synaptic proteins, upregulation of BDNF levels improves synaptic plasticity and alleviates cognitive dysfunction.DiscussionDOFF can improve cognitive dysfunction by regulating intestinal microbiota composition, enhancing intestinal barrier integrity in D-GAL-induced aging mice, improving neuroinflammation, and alleviating hippocampal neuron damage.